â€œTarekat Popolerâ€ dalam Fenomena Pembacaan Selawat NÃ¢rÃ®yah - Hasan, Nor (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2016)
The recitation of Selawat Nârîyah, as a religious ritual, performed by the Muslim community in Larangan Tokol Village, Pamekasan, East Java, has its own uniqueness within the process of its implementation and has an exceptional function from socio-religious-psychological point of view for its reciters. This article focuses its discussion mainly on the perception and motivation of the people in Larangan Tokol in recitation of Selawat Nârîyah. The article also observes the implication of recitation of Selawat Nârîyah for their socio-religious and psychological life. To Larangan Tokol people, Selawat Nârîyah has become a new religious tradition which should be maintained. It has been found that there is no such an obligation to adhere to certain Sufi order (tarekat) in order to perform the recitation of the selawat. However, there is a sort of psychological bond of guru (murshid) and murîd found in the membership (koloman) of recitation activity through what so-called tawassul. The tawassul is recited prior to the recitation of Selawat Nârîyah. The recitation of Selawat Nârîyah performed by Larangan Tokol people can be considered ?a new genre of tarekat?. The writer tends to call it ?Popular Tarekat? (an anonymous tarekat), i.e. an open Sufi order with no certain process of bay?ah but it has unabridged narration (sanad mutâwatir) to the Prophet Muhammad.